2014
DOI: 10.1177/0363546514560153
|View full text |Cite
|
Sign up to set email alerts
|

Altered Lower Extremity Movement Variability in Female Soccer Players During Side-Step Cutting After Anterior Cruciate Ligament Reconstruction

Abstract: While individuals who have had an ACLR exhibit mechanical knee stability before returning to sports, the observed increased movement variability during side-step cutting is likely reflective of altered neuromuscular control and may contribute to the known increased risk for ACL reinjury and knee osteoarthritis after return to sports participation. Improving the understanding of altered lower extremity coupling variability after ACLR will aid in the development of more effective rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 31 publications
0
54
2
Order By: Relevance
“…Significant findings were reported in 73% (n = 11/15). Greater variability in the injured group was evident in 67% (n = 10/15) of the studies, reduced variability in 20% (n = 3/15), and no difference observed between the two groups in 27% (n = 4/15) …”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Significant findings were reported in 73% (n = 11/15). Greater variability in the injured group was evident in 67% (n = 10/15) of the studies, reduced variability in 20% (n = 3/15), and no difference observed between the two groups in 27% (n = 4/15) …”
Section: Resultsmentioning
confidence: 91%
“…Overall findings revealed that 73% (n = 16/22) of studies reported a statistically significant difference in at least one dependent variable used to examine movement variability between injured subjects and uninjured controls. Injured subject groups demonstrated greater variability in 64% (n = 14/22) of the studies, reduced variability in 27% (n = 6/22), and no difference between groups was evident in 27% (n = 6/22) . Table presents the percentage of studies reporting greater, less, or no difference in variability when comparing injured subjects to uninjured controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations